Determining The Best Conditioning Method For Cut-Roses (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Conditioning is an important step in the flower maintenance post-harvest. It helps in increased storage  time and better shelf-life of the cut flowers. Conditioning provides the cut flowers with certain nutrients required for  their sustainability and prevents them from getting infected from some disease-causing microbes. People generally don’t  pay much importance to this step which leads to early decay and loss of their hard-earned flowers. Good conditioning  can help sort out this problem and help prevent the cut-flowers from getting bad, by providing ambient conditions for  the flower. Objective: The objectives of this study were to determine the best conditioning method for cut-Rose flowers  through scientific experiment and getting the views on the flower behavior under different conditions based on the visual  parameters. Methodology: The methodology undertaken for this work was a combination of experimental as well ob servational study. The experimental study was conducted in the housekeeping lab of IHM Pusa under the guidance of the  research guide and lab attendant. The observational study was conducted through a google form questionnaire and was  filled by some experts of the domain based on the visual parameters from the experiment conducted. Results: The most  favorable conditions for the cut-Rose were provided by SET ‘C’ from the experiment conducted which contained a solution of sucrose, citric acid and bleach in distilled water. Also, based on the visual parameters SET ‘C’ was voted 69.04%  as the best conditioner for cut-rose flower. Conclusion: Based on the results obtained from the experiment conducted  and through the observations made, it was concluded that the mixture containing sucrose, bleach and citric acid proved  to be helpful in conditioning of the flower in the best way, hence using the same can prevent the decay of cut flowers in  a substantial manner, increase the vase-life and in-turn help attain sustainability.
Keywords: Conditioning; Cut-flowers; Floriculture; Loose-flowers; Vase-life